Optimization of aerobic composting process of Camallia oleifera Seed Cake and its fertilizer efficiency. (June 2020) - Hu, Hualin; Li, Guanqiang; Song, Junrong; Wei, Fuxiao; Sun, Chao; Wang, Hong
Abstract: [Objective] In order to promote the development of camellia oil processing enterprises and solve the problem of waste of camellia oil enterprises, Camallia oleifera cake that tea saponin has been removed was composted to form organic fertilizer. [Method] The D-optimal mixture design method was utilized and the seed germinate rate was defined as evaluation index. The optimized formula was obtained by establishing regression equation and response surface optimization analysis based on single factor experiments. [Results] Under the condition that fermentation bacteria agent was 1% of the mixture, the best composting process was: 74.8% of remove tea saponin of Camallia oleifera cake (dry), 12.5% of pig manure (dry), 8.0% of straw and 4.7% of rice husk. Its seed germination rate predicted value was 150.56%, which was basically consistent with the measured value 151.23%; Its total nutrient content was 5.17%, which was up to organic fertilizer standard (NY525-2012). [Conclusion] The optimized formula can be used as composting process of Camallia oleifera cake, which has good repeatability, and provide scientific basis for rational utilization of Camallia oleifera cake and development of organic fertilizer.